(untitled) (Estudos em Design, 2021)
Recomendações para o design de jogos para jogadores com discalculia Matheus Cezarotto, New Mexico State University, USA matheus@nmsu.edu Abstract Educational digital games are interactive digital systems that promote learning experiences for the learner through a multimedia environment. Researchers and professionals have been using educational digital games as an intervention for children with dyscalculia. The literature demonstrates a limitation in research as regards these users’ experiences with games. This study offers a user-centered design framework to investigate specific game elements that can promote and sustain users’ motivation with dyscalculia during their neuropsychological treatment. It can be seen as an instance of applied research, with a descriptive goal and a qualitative data analysis approach. The study has used three main methods to inform the design of games that are better able to reach learners with dyscalculia: field research with both neuropsychological rehabilitation and game developers, and qualitative observations and interviews with players who have dyscalculia while they play math games. In addition, it offers a set of game design recommendations focusing on the motivation of children with dyscalculia.